The Jaw Epidemic: Recognition, Origins, Cures, and Prevention. (22nd July 2020) - Kahn, Sandra; Ehrlich, Paul; Feldman, Marcus; Sapolsky, Robert; Wong, Simon
Abstract: Contemporary humans are living very different lives from those of their ancestors, and some of the changes have had serious consequences for health. Multiple chronic "diseases of civilization, " such as cardiovascular problems, cancers, ADHD, and dementias are prevalent, increasing morbidity rates. Stress, including the disruption of traditional sleep patterns by modern lifestyles, plays a prominent role in the etiology of these diseases, including obstructive sleep apnea. Surprisingly, jaw shrinkage since the agricultural revolution, leading to an epidemic of crooked teeth, a lack of adequate space for the last molars (wisdom teeth), and constricted airways, is a major cause of sleep-related stress. Despite claims that the cause of this jaw epidemic is somehow genetic, the speed with which human jaws have changed, especially in the last few centuries, is much too fast to be evolutionary. Correlation in time and space strongly suggests the symptoms are phenotypic responses to a vast natural experiment—rapid and dramatic modifications of human physical and cultural environments. The agricultural and industrial revolutions have produced smaller jaws and less-toned muscles of the face and oropharynx, which contribute to the serious health problems mentioned above. The mechanism of change, research and clinical trials suggest, lies in orofacial posture, the way people now hold their jaws when not voluntarily moving them in speaking or eating and especially when sleeping. The critical resting oral posture has been disrupted in societies no longer hunting and gathering. Virtually all aspects of how modern people function and rest are radically different from those of our ancestors. We also briefly discuss treatment of jaw symptoms and possible clinical cures for individuals, as well as changes in society that might lead to better care and, ultimately, prevention.